Design and NMR characterization of reversible head-to-tail boronate-linked macrocyclic nucleic acids. Issue 14 (23rd March 2022) - Debiais, Mégane; Gimenez Molina, Alejandro; Müller, Sabine; Vasseur, Jean-Jacques; Barvik, Ivan; Baraguey, Carine; Smietana, Michael
Abstract : The construction of boronate ester-linked macrocyclic di- and trinucleotides by the head-to-tail assembly of a ribonucleotide precursor containing a boronic acid is reported. Abstract : Inspired by the ability of boronic acids to bind with compounds containing diol moieties, we envisioned the formation in solution of boronate ester-based macrocycles by the head-to-tail assembly of a nucleosidic precursor that contains both a boronic acid and the natural 2′, 3′-diol of ribose. DOSY NMR spectroscopy experiments in water and anhydrous DMF revealed the dynamic assembly of this precursor into dimeric and trimeric macrocycles in a concentration-dependent fashion as well as the reversibility of the self-assembly process. NMR experimental values and quantum mechanics calculations provided further insight into the sugar pucker conformation profile of these macrocycles.